KEDUDUKAN HUKUM ADAT DALAM HUKUM ISLAM TENTANG PELAKU MAKSIAT TERTENTU - Dedisyah Putra (IAIN Padangsidimpuan, 2023)
Adat or al-'adah is the oldest law in human history. Although Islam came after it, it still gives recognition to customs as long as it does not contradict the main principles in Islam called 'adat urf shahih. In both general and specific forms, adat can be used as a basis in Islamic law. This study will discuss the position of customary law in Islam related to certain perpetrators of immorality. This research is descriptive and uses literature sources. The results showed that in Islamic Law such as qisas (the law of retribution) and zina, this rule is not a new rule of law, but has long been in force in the customs of Arab society. The main change made by Islam to qisas was to include the principle of balance in its legal framework. The same goes for adultery. Therefore, there is a relationship between customary law and Islamic law in protecting human dignity in the context of benefit, providing lessons in law enforcement, and preventing people from falling into disrepute.